A Vision for agriculture in Trinidad and Tobago : selected articles Professor John Spence - Renwick, Shamin (UWI St AugustineTT, 2017)
Presents a series of articles by Prof Spence on agriculture, cocoa, food security, land use and related issues which appeared as a regular column in the Trinidad Express newspaer from May 2002 - February 2013.